2018
DOI: 10.1016/j.pmedr.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of intentional outdoor and indoor tanning among adolescents in the United States: Findings from the FLASHE survey

Abstract: A body of research has focused on adolescents' indoor tanning behaviors but relatively little is known about the prevalence of adolescents' intentional outdoor tanning (time spent outdoors to get a tan). The present study used data from the National Cancer Institute's 2014 Family Life, Activity, Sun, Health and Eating (FLASHE) cross-sectional survey to examine the prevalence and correlates of intentional outdoor and indoor tanning among adolescents in the United States. Both unadjusted (bivariate) and adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
7
2
Order By: Relevance
“…Forest plot for past‐year exposure in adults and college students. Table S1 Studies included in the meta‐analysis …”
mentioning
confidence: 99%
“…Forest plot for past‐year exposure in adults and college students. Table S1 Studies included in the meta‐analysis …”
mentioning
confidence: 99%
“…For example, young people who report frequent use of sunscreen, a skin protective behaviour, have been found to be more likely to use indoor tanning beds than people who use less sunscreen (Heckman et al, 2008). In a USA national study on adolescents' indoor and outdoor tanning behaviours, researchers found that outdoor tanning was significantly higher among non-Hispanic White girls and those who spent more time on cell phones (Niu et al, 2018). Indoor tanning rates were significantly higher among participants who spent more time on a computer or cell phone.…”
mentioning
confidence: 99%
“…This supposition is also in line with mood management theory, which argues that people often seek stimuli (be it a behavior or a media message) that help them achieve a more positive mood [33,34]. For example, recent work using the National Cancer Institute's Family Life, Activity, Sun, Health, and Eating (FLASHE) cross-sectional survey found that adolescents who reported being frequent outdoor tanners were more likely to experience loneliness than adolescents who reported they did not tan outdoors [7]. Although more research is needed to understand this relationship, it could be that adolescents in the survey tanned outdoors in order to reap the positive emotional benefits that could help them cope with feelings of loneliness.…”
Section: Emotions and Tanningmentioning
confidence: 98%
“…In US culture, tan skin is a commonly held beauty standard, and women often engage in outdoor or indoor tanning to achieve this standard. Although previous research has observed how media sources such as television [38] and magazines [35,36] influence tanning behaviors, a recent focus has been on social media [6,7]. Social media expands on traditional media platforms, as there are greater opportunities to interact within the media and exchange images.…”
Section: Social Media and Tanningmentioning
confidence: 99%
See 1 more Smart Citation